Study of the Use of Orifice as an Alternative for Steam Trap - Shakawi Efendy Jamaludin, Shakawi Efendy (2008)
The purpose of this research is to compare the effectiveness of the orifice plate steam trap over variable loads. This was achieved by conducting a few experiments and measuring the rate of steam loss under different condensate loads.